PHOTOVOICE ANALYSIS OF INDUSTRIAL PRACTICE EXPERIENCE: A COLLABORATIVE AUTOETHNOGRAPHY STUDY - Venisa Oktavia Putri Prabandari; Sri Sumarni; Fajar Danur Isnantyo (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
This study aims to examine the experience of implementing industrial practice with photovoice analysis through a collaborative autoethnography approach and reveal the factors that determine the success of industrial practice. This research is qualitative and uses a partial collaborative autoethnography approach. The source of research data is industrial practice activities. The sampling technique was carried out through purposive sampling. Data collection was carried out through critical autoethnography, observation, and Focus Group Discussion (FGD). The validity test technique used was FGD. Data analysis was carried out through content analysis. The results of this research include: first, the study of industrial practice learning experiences contained aspects of togetherness and cooperation (collaboration ability category); discussion (communication ability category); involvement, contribution, initiative, responsibility, and dedication (proactive category); implementation of knowledge, fast learning, self-development, obedience, and time management (adaptive category). Second, the factors determining the success of industrial practice include a supportive partner work environment, team solidarity, student competence, and student personality.